ENHANCING THE VIABILITY AND VIGOR OF SELECTED SUNFLOWER SEEDLINGS THROUGH HORMONAL PRIMING TECHNIQUES - A. R. Mohammed; N. N. Mutlak; D. K. Duraideh; S. E. Seadh (مجلة الأنبار للعلوم الزراعية, 2025)
This study was conducted in May 2022 and 2023 to assess the impact of different concentrations of the brassinolide hormone (0, 0.5, 1.0, and 1.5 mg L-1) on the viability and vigor of seedlings derived from specific sunflower varieties (Ishaqi-1, Aqmar, and Sakha). The factorial experiments consisted of four replications using a completely randomized design (CRD) for each. The results revealed that sunflower variety significantly influenced both the viability and vigor of their seedlings in the two years. The Sakha variety outperformed the others in producing high-quality seeds and robust seedlings during germination and vigor tests. Specifically, sunflower seeds primed with 1.0 mg L-1 of brassinolide hormone exhibited superior viability and seedling vigor compared to other test doses in both conventional germination tests and seedling characteristics